The Effect of Hands-on Practice on Improving the Innovation Ability of High School Students - Smart Safety Socket - Chiu-Cheng Kuo; Fei-Chuan Chen (Journal of ICT, Design, Engineering and Technological Science, 2018)
With the development of technology, electricity products are changing with each passing day, bringing many conveniences in people's lives. However, because of the increasing load on the socket, it is easy to produce electrical fires and cause loss of life and property under improper use conditions. This study aims to cultivate the practical ability of higher vocational students to use the knowledge and skills learned, improve the electrical safety of the socket, prevent electrical fires, and protect the lives and property of the people. Based on the safe use of the socket, the development and production of smart safety sockets will be carried out by the teachers and students of the higher vocational electrical engineering and the existing equipment and the relevant curriculum concepts. The features of this product include monitoring the power consumption of the socket, warning and power-off of the over-powered, and remotely controlling the power supply of the socket in combination with the mobile APP program. The study found that through the production of smart safety sockets, students can develop cooperative learning ability. The research also concluded that students could develop independent thinking and problem-solving skills through the production of smart safety socket. The results of this research show that smart safety sockets have practicality and enhance the safety of use. It is evident from the results of this research that students have certain help in the ability to innovate in the process of designing finished products.